Urtica pilulifera leaves extract mitigates cadmium induced hepatotoxicity via modulation of antioxidants, inflammatory markers and Nrf-2 signaling in mice - Hussein, Shaimaa; Ben Bacha, Abir; Alonazi, Mona; Alwaili, Maha Abdullah; Mobasher, Maysa A.; Alburae, Najla Ali; Banjabi, Abeer A.; El-Said, Karim Samy (Frontiers in Molecular Biosciences, 2024)
Introduction: Cadmium (Cd) is a harmful heavy metal that results in many toxic issues. Urtica pilulifera showed potential pharmaceutical applications. This study investigated the possible ameliorative mechanism of Urtica pilulifera leaves extract (UPLE) against hepatotoxicity induced by cadmium chloride (CdCl2) in mice.In vitro phytochemical screening and the metal-chelating activity of UPLE UPLE's phytochemical screening and metal-chelating ability in vitro were ascertained. Four groups of forty male mice were used (n=10). as follows; Group 1 (G1) was a negative control. G2 was injected i.p., with UPLE (100 mg/kg b. wt) daily. G3 was injected i.p., with Cd (5 mg/kg b. wt) daily. G4 was injected with Cd as in G3 and with UPLE as in G2. On day 11, the body weight changes were evaluated, blood, and sera serum samples were collected for hematological and biochemical assessments. Liver tissues were used for biochemical, molecular, and histopathological investigations.The results showed that UPLE contains promising secondary metabolites that considerably lessen the negative effects of Cd on the liver. Furthermore, UPLE inhibited oxidative stress and inflammation; restored antioxidant molecules; and promoted nuclearrelated factor-2 (Nrf-2) expression. Also, UPLE also improved the histopathological alterations induced by Cd.Discussion: This study explored the beneficial role of UPLE treatment in Cd-induced liver injury through enhancing Nrf-2 signaling and antioxidant enzyme genes expression in the liver of mice. Therefore, UPLE could have valuable implications against hepatotoxicity induced by environmental cadmium exposure. which can be used as a chelating agent against Cd.